Enzyme-responsive hydrogels: Development, characterisation and on-demand modulation of protease activity - Obenza Otero, Rebeca Lucia (2020)
Bioresponsive materials that are able to release their cargoes in response to disease-specific cues are of great interest for developing targeted therapeutics due to their potential to limit drug release to its site of action, thus minimising side effects. The use of proteases as triggers for biomaterial response is particularly attractive as upregulated activity of proteases, such as elastase, is related to several pathological states such as tissue destruction associated with chronic wounds and respiratory diseases. As elastase also possesses important functions that are crucial for maintaining a healthy status, full enzyme suppression is not desirable. Instead modulation of elastase activity to restore the natural protease/inhibitor balance that favours restoration of tissue integrity would be advantageous.